PENERAPAN PASAL 71D UNDANG-UNDANG NOMOR 35 TAHUN 2014 PERUBAHAN ATAS UNDANG-UNDANG NOMOR 23 TAHUN 2002 TENTANG PERLINDUNGAN ANAK TERHADAP KORBAN DI WILAYAH HUKUM KOTA PEKANBARU - Anita Rahmayuni; Emilda Firdaus; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
In Law Number 35 of 2014 Amendment to Law Number 23 of 2002 concerning Child Protection which has been regulated in Article 71D paragraph (1) states that every child who becomes a victim as referred to in Article 59 paragraph (2) letter b, letter d, letter f, letter h, letter i, and letter j have the right to submit to the court in the form of the right to restitution which is the responsibility of the perpetrators of crime, but in reality there are still many children who become victims of criminal offenses not getting the right of restitution. Until now there has been no seriousness of law enforcement officials in granting victims' rights regarding restitution so that victims have never been informed of the existence of such restitution rights. The purpose of this Thesis Writing, namely: First, Application of Article 71D of Law Number 35 Year 2014 Amendment to Law - Law Number 23 Year 2002 concerning Child Protection of Victims in the Legal Territory of Pekanbaru City, Secondly, obstacles in the Application of Article 71D of Law Number 35 Year 2014 Amendment to Law Number 23 Year 2002 concerning Child Protection of Victims in the Legal Territory of Pekanbaru City , Third, Ideally in the Application of Article 71D of Law Number 35 of 2014 Amendment to Law Number 23 of 2002 concerning Child Protection of Victims in the Legal Territory of Pekanbaru City.This type of research can be classified into the type of sociological juridical research, because in this study the author immediately conducts research on the place under study in order to provide a complete and clear picture of the problem to be studied, while the population and sample are all parties related to the problems examined this study, data sources used, primary data, secondary data and tertiary data, data collection techniques in this study with interviews, questionnaires and library dataThe results of the study can be concluded. First, the Application of Article 71D of Law Number 35 Year 2014 Amendment to Law Number 23 Year 2002 concerning Child Protection of Victims in the Legal Area of Pekanbaru City is proceeding well due to the lack of seriousness of law enforcement officials, especially the Pekanbaru City Prosecutor's Office in granting victims' rights regarding restitution. Second, Obstacles in the Application of Article 71D of Law Number 35 Year 2014 Amendments to Law Number 23 Year 2002 concerning Child Protection of Victims in the Legal Area of Pekanbaru City are caused by several factors, namely law factors, victim legal awareness and ability factors and the willingness of the defendant. Third, efforts made to overcome obstacles in the implementation of Article 281 of Law Number 22 Year 2009 concerning Road Traffic and Transportation Against Drivers of Underage Children by making improvements to Government Regulation Number 43 of 2017 concerning the Implementation of Restitution for Children Who Become Victims of Action Criminal.Keywords: Application - Child Protection - Victims - Restitution